Iron-Overload Conditions: Manifestations to the Kidney Organs - A Review - Nadia Larasinta Heriatmo; Ari Estuningtyas; Vivian Soetikno (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Excess iron is a risk factor for organ dysfunction and damage resulting in various organ diseases such as liver, heart, and kidney, diabetes mellitus, and neurodegenerative diseases. Iron overload in some individuals is caused by various factors, including genetic predisposition such as genetic hemochromatosis, repeated transfusion of red blood cells, and parenteral iron administration in conditions of transfusion-dependent anemia. A disturbance in the globin gene in diseases such as β-thalassemia major causes an imbalance of the globin chain, resulting in chronic anemia in the sufferer. It has been reported that the human body does not have a mechanism for eliminating excess iron levels. Routine transfusion has become a solution to overcome chronic anemia so that patients can maintain hemoglobin levels, and the result of this transfusion repetition is the accumulation of iron in various organs, such as the heart, liver, endocrine glands, pancreas, lungs, and kidneys. Excess iron can be toxic to the body due to the formation of harmful free radicals that can damage cells and tissues. An increase in excessive ROS can result in the saturation of the antioxidant system. The presence of free radicals can lead to damage and the occurrence of filtration dysfunction in the glomerulus.